Student teacher perceptions regarding career readiness and the effectiveness of a teacher preparation program - Dantas, Josue (Revista Eletrônica de Educação, 2016)
This study investigated student teachers perceptions regarding career readiness and the effectiveness of a teacher preparation program at Lynn University. In 2011, research conducted by McCulloch, Burris, and Ulmer emphasized that there are more than 1,400 colleges and universities in the United States preparing students to enter the teaching profession. Teacher preparation programs in the United States continue to graduate many individuals who do not go into a teaching career long-term. This study was designed to provide insight into whether or not student teacher perceptions might be used as a different perspective in terms of teacher preparation program evaluation. The investigation was conducted through the collection of data from a demographic survey and the administration of semi-structured interviews with the research participants. The data were organized through the categories of analysis proposed by the researcher: Category A: Effective classroom management skills; Category B: Programs and Endorsements; Category C: Instructor recommendations; Category D: Program requirements and features; Category E: Test preparation – State requirements and further combinations among them. The results of the study demonstrated that students recommend the inclusion of “hands on activities” as an alternative devoted to enhance the teacher preparation program. The findings of this study may be useful to contribute to the development of teacher preparation programs, to educational research literature, and also in terms of planning and implementing effective professional development for teachers. Keywords: Teacher preparation. Career readiness. Newly graduated teachers. Program evaluation.